Ulcerative dermatitis in wild dusky grouper Epinephelus marginatus (Lowe) from Libyan waters. Issue 12 (4th May 2016) - Rizgalla, J; Bron, J E; Shinn, A P; Herath, T K; Paladini, G; Ferguson, H W
Abstract: In the period 2013–2015, wild dusky grouper, Epinephelus marginatus (Lowe), caught in Libyan coastal waters and ranging in size from 42 to 92 cm in total length, were observed to have distinctive skin lesions of unknown aetiology. Histopathologically, the lesions comprised a multifocal, unilateral or bilateral dermatitis, involving the epidermis, superficial dermis and scale pockets, and sometimes, in severe cases, the hypodermis. Severe lesions had marked epidermal spongiosis progressing to ulceration. Healing was observed in some fish. Bacteria and fungi could be isolated from severe lesions, although they were not seen histopathologically in early‐stage lesions. By contrast, metazoan parasite eggs were observed in the dermis and epidermis of some fish with mild and moderate dermatitis. Unidentified gravid digenean trematode parasites carrying similar eggs were also seen within the blood vessels of the deep and superficial dermis. The cause of this distinctive condition, termed dusky grouper dermatitis (DGD), and its potential impact upon already threatened Mediterranean wild dusky grouper populations and upon cultured grouper more widely have yet to be established.